Recombinant adiponectin alleviates abortion in mice by regulating Th17/Treg imbalance via p38MAPK-STAT5 pathway. Issue 4 (28th November 2018) - Li, Weihong; Geng, Lihong; Liu, Xiru; Gui, Wenwu; Qi, Hongbo
Abstract: Recurrent spontaneous abortion is associated with abnormal maternal tolerance to the semi-allogenic fetus, wherein the Th17/Treg axis plays a crucial role. Adiponectin (APN) is an adipocytokine that is shown to be a novel negative T-cell regulator and induce immune tolerance. The CBA/J × DBA/2 mating was used as an abortion-prone model to investigate whether the addition of recombinant adiponectin (rAPN) improves the pregnancy outcome. Recombinant adiponectin therapy reduced the abortion rate in abortion-prone model. It skewed the ability of serum cytokine production toward a Treg bias and induced APN production. Flow cytometry revealed that rAPN administration expanded the splenic CD4 + CD25 + regulatory T-cell (Treg) population and reduced the Th17 cell populations in CBA/J × DBA/2 matings. RT-PCR revealed that rAPN administration induced the expression of AdipoR1 and AdipoR2 mRNA at the maternofetal interface. Recombinant adiponectin administration induced FoxP3 and reduced RORγt expressions at the maternofetal interface. In vitro experiment also showed that rAPN treatment enhanced the FoxP3 mRNA and protein expression and decreased the RORγt expression in splenic lymphocytes of abortion-prone mice. Blocking the different signal transduction pathways downstream of APN, p38MAPK inhibitor (SB203580) and STAT5 inhibitor (Pimozide) could abrogate the regulatory effect of rAPN on FoxP3 and RORγt expression, while STAT3 inhibitor (Stattic) and AMPK inhibitor (p5499) did not exert any influence. Thus, the current results demonstrated that rAPN therapy improves pregnancy outcome in a murine model of abortion by expanding the Treg cell population and function and decreasing the Th17 cell population and function via a p38MAPK-STAT5 pathway. Abstract : Adiponectin, which is essential for lipid metabolism and homeostasis, is beneficial for pregnancy outcome through improving Th17 and Treg populations; the process is associated with the activation of p38MAPK-STAT5 pathway.